KOLABORASI PERGURUAN TINGGI DAN MASYARAKAT UNTUK PENGEMBANGAN DESA TIMORO BERKELANJUTAN MELALUI KKN MAHASISWA UNIVERSITAS MUHAMMADIYAH MAMUJU - Kurnia, Kurnia; Yati Heriyati; Abdul Wahab (Bajang Institute, 2025)
The Community Service Program (Kuliah Kerja Nyata/KKN) represented a tangible implementation of the Tri Dharma of Higher Education, particularly in the area of community engagement. This article discussed an integrated community empowerment initiative in Timoro Village, Tabulahan Sub-district, Mamasa Regency, West Sulawesi, which was carried out by students of Universitas Muhammadiyah Mamuju. The program was designed to address local issues such as low awareness of Clean and Healthy Living Behavior (PHBS), suboptimal waste management, and the underdeveloped potential of local economic products. The method employed was a participatory approach, involving students, village authorities, and community members in every stage of the activities, ranging from problem identification, planning, and implementation to evaluation. The results indicated an increase in community awareness of the importance of PHBS and stunting prevention, the establishment of routine practices for maintaining environmental cleanliness, as well as the creation of innovative local products such as pineapple jam and dodol, which had the potential to enhance economic self-reliance. In addition to delivering tangible benefits for the community, the program also strengthened students’ competencies in leadership, communication, and teamwork. The study concluded that the integration of health education, environmental management, and local product innovation could serve as a sustainable and replicable model of community service in rural areas of Indonesia.